ANALISIS PENGENDALIAN INTERN ATAS PENERIMAAN KAS PADA PT. MANDALA MULTIFINANCE, TBK CABANG MANADO - Ogi, Gratia Patricia; Pangemanan, Sifrid S; Pontoh, Winston (Universitas Sam Ratulangi, 2020)
In a business activity, both large and small companies the goal obtained is the maximum profit in order to maintain the business. To achieve these objectives, it is necessary to have an Inter Control System. The object of research is PT. Mandala Multifinance, Tbk Manado branch engaged in vehicle transportation services. This study discusses to analyze the internal control system specifically for cash receipts at PT. Mandala Multifinance, Tbk Manado Branch. The research method used is descriptive qualitative. The results showed that the Internal Control System at PT. Mandala Multifinance, Tbk Manado branch has well had a Company Internal Policy (KIP) which is implemented to avoid fraud when receiving company cash.